No concessions : the life of Yap Thiam Hien, Indonesian human rights lawyer - Lev, Daniel S. (Critical dialogues in Southeast Asian studies., 2011)
A biography of human rights lawyer Yap Thiam Hien (1913-1989) that focuses on the country's contemporary political turmoil and struggle for human rights, the workings of Indonesia's legal system, and the history of the Chinese community there.--